2022
DOI: 10.1111/acps.13515
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low‐dose quetiapine‐use on glycosylated hemoglobin, triglyceride and cholesterol levels

Abstract: Objective Quetiapine use at standard doses has been associated with hyperglycemia and dyslipidemia. However, whether even frequently prescribed low‐dose quetiapine results in significant metabolic disturbances remains unclear. Thus, this study aimed to investigate the association between off‐label, low‐dose quetiapine and changes in glycosylated hemoglobin (HbA1c) levels/lipid parameters. Methods We identified new users of low‐dose quetiapine (≤50 mg tablets) in Denmark 2008–2018 with measurements of HbA1c, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…Regarding metabolic side effects, considering the dosage of quetiapine in our hospital (at the time of discharge, 13 of 14 patients were under 50 mg/day), the effect of multiple receptor blockade with quetiapine may not be significant. 10,11 BZD/non-BZD is a risk factor for falls, cognitive impairment, and delirium. [12][13][14] It is reported that BZD/non-BZD could cause dependence within months, even with regular doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding metabolic side effects, considering the dosage of quetiapine in our hospital (at the time of discharge, 13 of 14 patients were under 50 mg/day), the effect of multiple receptor blockade with quetiapine may not be significant. 10,11 BZD/non-BZD is a risk factor for falls, cognitive impairment, and delirium. [12][13][14] It is reported that BZD/non-BZD could cause dependence within months, even with regular doses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reducing the dosage was difficult. Regarding metabolic side effects, considering the dosage of quetiapine in our hospital (at the time of discharge, 13 of 14 patients were under 50 mg/day), the effect of multiple receptor blockade with quetiapine may not be significant 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…The association of quetiapine with weight gain is also well-known, with novel data warning that even low-dose quetiapine is associated with this adverse effect (Hojlund et al 2023 ). This appears particularly relevant as low-dose quetiapine is frequently prescribed as an add-on drug targeting secondary symptoms such as insomnia and agitation in a transdiagnostic fashion (de Bardeci et al 2023 ; Pringsheim and Gardner 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association of quetiapine with weight gain is also well-known, with novel data warning that even lowdose quetiapine is associated with this adverse effect (Hojlund et al, 2023). This appears particularly relevant as low-dose quetiapine is frequently prescribed as an add-on drug targeting secondary symptoms such as insomnia and agitation in a transdiagnostic fashion (de Bardeci et al, 2023; Pringsheim and Gardner, 2014).…”
Section: Discussionmentioning
confidence: 99%